Recommendations for Selecting Houses in the Bintaro Area Using the AHP Method for Property Sales Companies - Zulfitriansyah, Fadillah; Sutomo, Rudi (Journal of Applied Research In Computer Science and Information Systems, 2023)
This research aims to overcome customer difficulties in choosing a house in the Bintaro area, especially in the context of Property Sales Companies. Customers often face challenges in navigating the process of selecting a home that fits their preferences and needs. The complexity of very complicated and unstructured situations is one of the main obstacles, so an approach is needed that can simplify the process. In order to overcome these problems, this research proposes the application of two main approaches, namely Process Hierarchy Analysis (AHP) and system prototype development. Using AHP, variables such as price, land area, building area, number of bedrooms, and distance from the city center were identified as key elements that were the focus of the research. A criteria priority matrix will be created based on these variables to become the basis for determining optimal housing choices. In addition, this research also tries to overcome barriers in housing selection by adopting a prototype approach to system development. Thus, it is hoped that the system developed can provide a more effective and efficient solution in simplifying the home selection process for customers. By considering the findings of the AHP calculation method. It is hoped that this research can make a significant contribution in improving the house selection process in the Bintaro area. With better solutions, it is hoped that Property Sales Companies can more effectively overcome challenges in meeting customer preferences, thereby increasing their satisfaction.